2018
DOI: 10.1159/000487730
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Tumor Suppressor Role of CEACAM1 in Multiple Myeloma

Abstract: Background/Aims: Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1), also known as CD66a, is a member of the immunoglobulin (Ig) superfamily that belongs to the carcinoembryonic antigen (CEA) family which plays a dual role in cancer. Previous studies showed high expression of CEACAM1 in multiple myeloma (MM). The aim of this study was to investigate the biological consequences of CEACAM1 overexpression in MM. Methods: pEGFP-N1-CEACAM1 and pcDNA3.1-CEACAM1 expression plasmids were transfected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Therefore, the role of CEACAM1 in cancer cells may be different from its role of inhibiting anti-tumor immune responses in T cells. Our findings were supported by the previous research pointing to the tumor suppressor role of CEACAM1 4755 . A most recent study suggested that CEACAM1 overexpression significantly suppressed cancer cell proliferation, induced cancer cell apoptosis, and inhibited cancer cell invasion and migration possibly through activation of caspase-3 and downregulation of MMP-2 and MMP-9 47 .…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the role of CEACAM1 in cancer cells may be different from its role of inhibiting anti-tumor immune responses in T cells. Our findings were supported by the previous research pointing to the tumor suppressor role of CEACAM1 4755 . A most recent study suggested that CEACAM1 overexpression significantly suppressed cancer cell proliferation, induced cancer cell apoptosis, and inhibited cancer cell invasion and migration possibly through activation of caspase-3 and downregulation of MMP-2 and MMP-9 47 .…”
Section: Discussionsupporting
confidence: 91%
“…Previous study has suggested SMAD7 can induce growth and inhibit apoptosis in colon adenocarcinoma cells and acts as a tumor promoter [35], indicating that miR-581-mediated apoptosis might be SMAD7/TGFβ-pathway-independent. Moreover, in the results of miR-581 target genes, TNFSF10 [36,37], HMGA2 [38], CEACAM1 [39,40], and mTOR [41] have been reported to be involved in proliferation and apoptosis in a number of cancers. There is a strong possibility that miR-581 regulates CRC proliferation and apoptosis by targeting these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to unique sialofucosylated glycoforms within its GPI anchor, CEA was found to bind to L-selectin and E-selectin, therefore mediating cell adhesion. CEA-CAM 1 is tumor suppressing through decreasing cell proliferation and metastasis, while CEA-CAM-5 is tumor promoting through inhibiting colon cell differentiation, anoikis and apoptosis (65,66). This is attributed to CEA-CAM-5 co-localization and subsequent activation of a5ß1 integrin signal transduction, triggering PI3K/AKT activity (67).…”
Section: Pathway and Functionmentioning
confidence: 99%